Poder e democracia: limites da soberania popular: - Costa, Matheus Bento (2019)
This paper aims to discuss the issue of popular power or popular sovereignty, a concept inevitably intertwined with the idea of democracy, hailed as the best form of government possible by contemporary scholars. The approach chosen was eminently theoretical from the standpoint of the key concepts and principles related to democracy and which support the idea that government based on popular sovereignty is the best option for the contemporary world. This kind of theoretical discussion is salutary for two reasons. The first reason is that, although it is considered the best form, there is no consensus on what the democratic form itself is, changing according to the ideological position adopted; the second reason is the increasing apathy of the people in relation to the politics and the democratic form perceived in some national surveys. In view of these dissonances and approaching the concepts of politics, sovereignty, freedom, equality and of democracy, it’s inquired about the superiority nature of popular government; more specifically about the popular power under which it rests, whether it is always a good thing or not.